THE ANALYSIS OF PROPPING AGENT GRANULES MOVEMENT IN THE CRACKS AND PRECONDITION OF GROWTH OF PROPPING AGENT LAYER IN HYDRAULIC FRACTURING - Дяченко, Юлія Григорівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this article the author analyzes the effectiveness of the hydraulic fracturing of the layer (LHF), which is primarily defined by the quality of propping agent fixing cracks and crack conductivity. The article covers possible forms of created cracks and the data of deep penetration of propping agent into the crack, but also there are given the conditions of crack closing at the bore drilling zone. There were characterized the main factors of affecting the growth of propping agent layer and the nature of its stuffing it into the cracks.